RETRACTED: Targeting and Therapy of Glioblastoma in a Mouse Model Using Exosomes Derived From Natural Killer Cells - Zhu, Liya; Oh, Ji Min; Gangadaran, Prakash; Kalimuthu, Senthilkumar; Baek, Se Hwan; Jeong, Shin Young; Lee, Sang-Woo; Lee, Jaetae; Ahn, Byeong-Cheol (Frontiers in Immunology, 2018)
Objective Glioblastoma is a highly aggressive primary brain tumor that is resistant to radiotherapy and chemotherapy. Natural killer (NK) cells have been used to treat incurable cancers. Recent studies have investigated the effectiveness of NK-cell-derived exosomes (NK-Exo) for treating incurable cancers such as melanoma, leukemia, and neuroblastoma; however, NK-Exo have not been used to treat glioblastoma. In the present study, we investigated the antitumor effects of NK-Exo against aggressive glioblastoma both in vitro and in vivo and determined the tumor-targeting ability of NK-Exo by performing fluorescence imaging. Methods U87/MG cells were transfected with the enhanced firefly luciferase (effluc) and thy1.1 genes; thy1.1-positive cells were selected using microbeads. U87/MG/F cells were assessed by reverse transcription polymerase chain reaction (RT-PCR), western blotting, and luciferase-activity assays. NK-Exo were isolated by ultracentrifugation, purified by density gradient centrifugation, and characterized by transmission electron microscopy, dynamic light scattering (DLS), nanoparticle-tracking analysis (NTA), and western blotting. Cytokine levels in NK-Exo were compared to those in NK cells and NK-cell medium by performing an enzyme-linked immunosorbent assay (ELISA). NK-Exo-induced apoptosis of cancer cells was confirmed by flow cytometry and western blotting. In vivo therapeutic effects and specificity of NK-Exo against glioblastoma were assessed in a xenograft mouse model by fluorescence imaging. Xenograft mice were treated with NK-Exo, which was administered seven times through the tail vein. Tumor growth was monitored by bioluminescence imaging (BLI), and tumor volume was measured by ultrasound imaging. The mice were intraperitoneally injected with dextran sulfate 2 h before NK-Exo injection to decrease the liver uptake and increase the tumor specificity of NK-Exo. Results RT-PCR and western blotting confirmed the gene and protein expression of effluc in U87/MG/F cells, with the bioluminescence activity of U87/MG/F cells increasing with an increase in cell number. NTA and DLS results indicated that the size of NK-Exo was ~100 nm, and the western blot results confirmed that NK-Exo expressed exosome markers CD63 and Alix. We confirmed the in vitro cytotoxic effects of NK-Exo on U87/MG/F cells by performing BLI, and the killing effect on U87/MG and U87MG/F cells was measured by CCK-8 and MTT assays (p < 0.001). ELISA results indicated that NK-Exo contained tumor necrosis factor-α and granzyme B. In vivo NK-Exo treatment inhibited tumor growth compared to in control mice (p < 0.001), and pretreatment of xenograft mice with dextran sulfate 2 h before NK-Exo treatment increased the antitumor effect of NK-Exo (p < 0.01) compared to in control and NK-Exo-alone-treated mice. Conclusion NK-Exo targeted and exerted antitumor effects on glioblastoma cells both in vitro and in vivo, suggesting their utility in treating incurable glioblastoma.